Caracterización de Arcillas del Estado de Guanajuato y su Potencial Aplicación en Cerámica - Ramos Ramírez, Esthela; Guzmán Andrade, Juan José; Sandoval Juárez, Ma. Carmen; Gallaga Ortega, Yolanda (Acta Universitaria, 2002)
The ceramic industry is a very important activity in several municipalities of the state of Guanajuato, where a significant and constant demand is kept for clay as raw material to formulate pastes used in the manufacturing of utilitarian and ornamental ceramic products. Traditionally, there have existed evidences about important clay deposits in the state of Guanajuato with suitable ceramic properties, which have not been completely characterized or quantified. Thus, considering the relevance of this raw materials to the ceramic industry in the region, as well as the difficulties to dispose of ceramic commercial materials with high and homogeneous quality at a low cost, the Centro de Investigaciones en Química Inorgánica and the Dirección de Fomento Minero del Estado de Guanajuato established a collaborating project focused on the study of the selected clay deposits and taking into account the following aspects: clay characterization, evaluation of the ceramic properties and calculation of the existing reserves. In this paper the results of the chemical and mineralogical characterization of the clays in the selected zone samples are presented. The results were reviewed with respect to the obtained values in the characterization of the commercial pastes ordinarily used by the potters in order to establish an initial estimation about the real potential of the clay deposits studied.
Keywords: Array; Array; Array; Array